Eccentric Strength Training: A Review of the Available Technology. Issue 1 (February 2017) - Tinwala, Farhan; Cronin, John; Haemmerle, Enrico; Ross, Angus
Abstract : ABSTRACT: ECCENTRIC (ECC) STRENGTH TRAINING IS BECOMING INCREASINGLY POPULAR AMONG STRENGTH AND CONDITIONING COACHES AND PRACTITIONERS GIVEN THE PROVEN BENEFITS FOR PERFORMANCE IMPROVEMENTS, INJURY PREVENTION AND REHABILITATION. THE PURPOSE OF THIS ARTICLE IS TO UNDERSTAND THE DEVICES THAT ARE AVAILABLE FOR THE TRAINING OF ECC STRENGTH, THE TECHNOLOGY INVOLVED, AND THE ASSOCIATED ADVANTAGES AND DISADVANTAGES. IT IS HOPED THAT WITH THIS KNOWLEDGE THE PRACTITIONER IS BETTER INFORMED AT MATCHING ECC STRENGTH TRAINING NEEDS WITH THE APPROPRIATE TECHNOLOGY. FOR A VIDEO ABSTRACT DESCRIBING THIS ISSUE, SEE VIDEO, SUPPLEMENTAL DIGITAL CONTENT 1, http://links.lww.com/SCJ/A198 . Abstract : Supplemental Digital Content is Available in the Text.